Tipologi Pemikiran Cendikiawan Muslim - Ridwan, Ridwan; Rosyidi, Abdul Wahab (ULUL ALBAB Jurnal Studi Islam, 2004)
In the process of the development of intellectualsm, the role of Moslem scholars who were successful to make a dynamic atmosphere in Islamic thoughts to point out. They’re popular and well-socialized thoughts develop and bring posit if on the knowledge and the perception of religion in the society. The development of the scholar's Islamic thought has different characteristic and pattern which is interesting to analyze. The purpose of analysis is to enlarge our knowledge on the Islamic thought, especially those which were written in daily newspaper" Jawa Pos" during the Romadhon 1425 H. To sum up, an essay which were written by same Moslem scholars has different characteristic: first, the understandings about " Fasting" are varied. The scholar's have different perception on it. Second the different point of view creates a different way of thingking. Those are: Formalistic, Transformatic, Realistic, and Idealistic which all lead to the socio- cultural change.